Intervertebral disc penetration by antibiotics used prophylactically in spinal surgery: implications for the current standards and treatment of disc infections - Capoor, Manu N; Lochman, Jan; McDowell, Andrew; Schmitz, Jonathan E; Solansky, Martin; Zapletalova, Martina; Alamin, Todd F; Coscia, Michael F; Garfin, Steven R; Jancalek, Radim; Ruzicka, Filip; Shamie, A Nick; et al. (European spine journal, 2019)
PURPOSE: The presence of Propionibacterium acnes in a substantial component of resected disc specimens obtained from patients undergoing discectomy or microdiscectomy has led to the suggestion that this prominent human skin and oral commensal may exacerbate the pathology of degenerative disc disease. This hypothesis, therefore, raises the exciting possibility that antibiotics could play an important role in treating this debilitating condition. To date, however, little information about antibiotic penetration into the intervertebral disc is available. METHODS: Intervertebral disc tissue obtained from 54 microdiscectomy patients given prophylactic cefazolin (n = 25), clindamycin (n = 17) or vancomycin (n = 12) was assayed by high-performance liquid chromatography, with cefaclor as an internal standard, to determine the concentration of antibiotic penetrating into the disc tissue. RESULTS: Intervertebral disc tissues from patients receiving the positively charged antibiotic clindamycin contained a significantly greater percentage of the antibacterial dose than the tissue from patients receiving negatively charged cefazolin (P < 0.0001) and vancomycin, which has a slight positive charge (P < 0.0001). CONCLUSION: Positively charged antibiotics appear more appropriate for future studies investigating potential options for the treatment of low-virulence disc infections. These slides can be retrieved under Electronic Supplementary Material.
Keywords: Cefazolin; vankomycin; Humans; Clindamycin; cefazolin; Cutibacterium acnes; Gram-Positive Bacterial Infections; dospělí; degenerace meziobratlové ploténky; lidé; antibakteriální látky; Propionibacterium acnes; výhřez meziobratlové ploténky; Vancomycin; grampozitivní bakteriální infekce; Degenerative disc disease; Adult; Intervertebral Disc; Anti-Bacterial Agents; Biofilm; Intervertebral Disc Degeneration; klindamycin; Intervertebral Disc Displacement; Surgical prophylaxis; meziobratlová ploténka